Implementation of the Kahoot Application in Volleyball Learning for Class X at SMAN 9 Semarang - Muhammad Zaki Ambari; Bertika Kusuma Prastiwi; Muhammad Alimin (Universitas Sebelas Maret, 2024)
The aim of the research is to determine the implementation of the Kahoot application in learning volley ball in class X at SMAN 9 Semarang. The method applied is descriptive qualitative, this is done to find out phenomena directly in the field, so that researchers know the situation and conditions in reality. Sources of research data are tests, interviews, observations and documentation. The results of this research are that the factors underlying the use of the Kahoot application are technological disruption, the implementation of the Merdeka curriculum at SMAN 9 Semarang, and the degradation of learning activities. The steps in using Kahoot are that the teacher sets up a Kahoot account and shares the Kahoot link, then students answer questions according to the instructions, view the results, and discuss the learning outcomes listed in the Kahoot application. Furthermore, the benefits of using the Kahoot application in learning volly ball are that it fosters interactive, creative and innovative learning, provides learning that focuses on students, and gives the impression of learning that is integrated with technology.